Zimbabwean women"s experiences at Johanne Masowe WeChishanu Apostolic churches" open ground gatherings - Vengesai, Priccilar (HTS teologiese studies, 2023)
The Constitution of Zimbabwe guarantees religious freedoms and freedom of association including for religious purposes. While people can gather for religious purposes, the main thrust of this paper is to investigate and unpack environmental crises caused by Christian gatherings and how women are affected by these environmental crises. The article focuses on the Johanne Masowe WeChishanu Apostolic churches. Environmental rights in terms of the Constitution recognize the need for one to be in a healthy environment. It also imposes an obligation for the non- occurrence of land pollution, land degradation, or destruction of the ecology and the advancement of conservation and ecological sustenance. Through observation, it was established that the Johanne Masowe WeChishanu Apostolic churches hold their church services in an open ground with no ablution facilities and no availability of critical basic resources such as water and medical facilities. The paper contends that the environmental crisis caused by open gatherings affect women and men differently. Equally, the effects of climate change leave women in an unhealthy environment during church gatherings. It is further argued that such consistent gatherings in one place cause environmental degradation and deforestation. Leaning on the feminist social justice theory, this paper advocates consideration of approximately prepared meeting places for the Johanne Masowe WeChishanu Apostolic churches gatherings inclusive of provision of basic ablution and clean water facilities.Contribution: This article makes a significant contribution to the study of gender in the context of environmental challenges and recommends greater involvement of women in the fight against environmental crises.